Two New Generalized Parametric Intuitionistic Fuzzy Information Measures (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In today’s life human thinking depends on uncertainty and fuzziness.Predominantly in the faltering atmosphere, the precise value of some factors is difficult to measure. Though, it can be easily approximated by intuitionistic fuzzy linguistic term in the real-life world problem. To deal with such uncertainty and fuzziness in present communication fuzzy information ordered measure defined on intuitionistic fuzzy set. Baiget. al.[18] and O. Prakash[19] defined a fuzzy entropy measure on fuzzy set and we generalize this entropy on intuitionistic fuzzy set. To verify the validity of proposed measure some properties, tables and numerical example is given.